Storytelling, resilience and transitional justice: Reversing narrative social bulimia - Clark, Janine Natalya (Theoretical criminology, 2022)
This article is about storytelling and transitional justice. Utilizing the late Jock Young’s concept of social bulimia, it uses the author’s fieldwork with victims-/survivors of conflict-related sexual violence in Bosnia-Herzegovina to demonstrate that storytelling can become a social bulimic process of absorption and expulsion. The article’s key aim is to explore ways of addressing this. In so doing, it draws on the neurological concept of plasticity. Emphasizing the importance of ‘narrative plasticity’ in the sense of giving victims-/survivors more control over their stories, and linking the concept to resilience, it argues that narrative plasticity can help to address the absorption and exclusion dynamics of social bulimia—and thereby contribute to moving transitional justice in a new ecological direction.